(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The formation of students' reading comprehension skills is one of the important aspects of teaching a foreign language, and it involves the development of not only written, but also communication skills. This article aims to study the opinions of methodologists who have made effective contributions to the methodology of foreign language teaching by using the task-based teaching method in foreign language teaching. Формирование у учащихся навыков понимания прочитанного является одним из важных аспектов обучения иностранному языку и предполагает развитие не только письменных, но и коммуникативных навыков. Целью данной статьи является изучение мнений методистов, которые внесли эффективный вклад в методику преподавания иностранного языка, используя метод задач при обучении иностранному языку.